An Empirical Exploration of Volunteer Management Theory and Practice: Considerations for Sport Events in a “Post-COVID-19” World - Power, Gareth; Nedvetskaya, Olesya (Frontiers in Sports and Active Living, 2022)
The existing literature highlights some universal principles that are widely accepted as a good volunteer management practice, e. g., volunteer appreciation and recognition, provision of meaningful roles, effective communication, and the importance of relational connection, just to name a few. Yet, it can be argued that a gap exists in the relationship between volunteer management theory and practice in the context of large sport events. For example, published evidence shows that volunteer programs often lack effective planning and management to achieve successful program results. On one hand, this can be attributable to limited knowledge about volunteers' characteristics and motivations, their lived experiences, the processes of volunteering, and the actual volunteer management practices. On the other hand, a lack of the right mechanisms (e.g., political will, financial, and managerial resources) in place before and throughout the event lifespan intensifies this disconnect. The aim of this research, therefore, was to critically examine the reasons behind this theory-practice divide in volunteer–volunteer management relationship and its potential impact on volunteer experiences and volunteer program outcomes, particularly in the context of the COVID-19 pandemic and its implications for sport event organizers and volunteer managers in the UK. A mixed methods approach was adopted for this study: a survey conducted with volunteers (n = 101) combined with a series of interviews with volunteers (n = 8) and volunteer managers (n = 6). The study identified some potential challenges facing volunteer programs associated with large sport events post-pandemic, particularly in relation to volunteer recruitment, volunteer management, and safety concerns affecting volunteer confidence to re-engage in volunteering. These challenges carry with them certain resource implications that event organizers need to consider to effectively run volunteer programs and support volunteers in engagement and re-engagement following the pandemic, as well as to harness opportunities the pandemic has potentially created to successfully re-emerge from the shadow of COVID-19. The study provides specific recommendations to inform event planning and delivery to enhance volunteer experiences and, ultimately, outcomes of volunteer programs associated with large sport events.